A Study on Consumer Behaviour towards Purchase Decision of Household Furniture in Dharmapuri District - PRIYANKA, S.; PRIYANKA, S.; GOVINDARAJ, V. (International Journal of Psychosocial Rehabilitation, 2020)
Today furniture is necessity for any household and it has been considered as essential household items. Furniture facilitates comfort to relax and to carry out domestic affairs for the family members. To accommodate visitors, offices and business houses are also equipped with trendy furniture. Any organization like educational institutions, meeting halls and marriage halls, also use plastic furniture to enhance their ambiance. Today there are many branded furniture company which are manufacturing plastic furniture. The plastic furniture observed by the customers is portable and attractive and it enhances the social status of customers. Earlier steel and wooden furniture used where users find difficulties. However, the hassle free plastic furniture has replaced steel and wooden furniture. Plastic furniture is easy to maintain and occupy little space and easy to accommodate. In this study, an attempt is made to study the customers’ attitude towards branded furniture in Dharmapuri district.